Flesh flies (Diptera: Sarcophagidae: Sarcophaginae) from the Colombian Guajira biogeographic province, an approach to their ecology and distribution (2017)
ABSTRACT: Sarcophaginae is the most diverse subfamily of Sarcophagidae with 51 genera and more than 1,800 species and it is widely distributed in the Neotropical Region. Sarcophaginae flies of forest, rural, and urban habitats of the seven departments comprising the Colombian Guajira biogeographic province were surveyed. Van Someren Rydon traps baited with fermented fruit, decomposing fish, and human feces were active for 72 hours with samples collected every 12 hours (day/night) between 2010 and 2014. A total of 14,223 sarcophagines (78% females and 22% males) were collected, which belong to 28 species of nine genera. Oxyvinia excisa (Lopes, 1950) is a new record for Colombia. The richest genera were Oxysarcodexia Townsend, 1917 and Peckia Robineau-Desvoidy, 1830, with eleven and nine species, respectively. Some of the species with the highest affinity to urban habitats were Oxysarcodexia bakeri (Aldrich, 1916), Oxysarcodexia aurata (Macquart, 1851), and Oxysarcodexia timida (Aldrich, 1916); to rural habitats were Oxysarcodexia diana (Lopes, 1933), Ravinia columbiana (Lopes, 1962), and Ravinia effrenata (Walker, 1861); and to forest habitats were Helicobia rapax (Walker, 1849), Oxysarcodexia avuncula (Lopes, 1933), and Oxysarcodexia major Lopes, 1946. We also discuss diet, habitat, and activity periods of the species. Species composition of Sarcophaginae in the Guajira province was very homogenous across the habitats, with the forest as the richest habitat. Scavenger habits of Sarcophaginae are confirmed, as well as their strong association with anthropic environments.